The Effects of Knowledge Base Diversity on Cross-Industry Innovation Performance: The Moderating Role of Network Embeddedness - Yang Zhou; Chunyu Meng; Xin Chen (Complexity)
To reveal the impact of knowledge base diversity (KBD) and network embeddedness on cross-industry innovation performance (CIP), we performed an empirical hierarchical regression analysis using patent data from the mobile phone industry. The results show the following. (1) There was an inverted U-shaped relationship between relevant KBD and CIP and a U-shaped relationship between nonrelevant KBD and CIP. (2) The effects of relevant KBD on CIP were negatively moderated by an enterprise’s structural embeddedness (SE) and relational embeddedness (RE) in the innovation network. (3) The effects of nonrelevant KBD on CIP were positively moderated by an enterprise’s SE and RE in the innovation network. The findings contribute to the body of knowledge on the influencing factors of CIP and provide guidance for cross-industry innovation practice.